"n Eksegese van Jeremia 7:1–15 - Silva, A. A. da (Hervormde teologiese studies, 1985)
Jeremia 7:1–1 5 is a judgment prophecy in the style of a court verdict. Each of the five subdivisions is functional: The introduction underlines the divine authority of the judgment; the part between the introduction and the charge states the 'Law' by which the nation's transgressions would be tried; the charge stipulates the nature and gravity of the transgressions; the part between the charge and the sentence quotes a previous 'case' and the sentence stipulates that the punishment will be the same as the punishment executed against Shilo: the temple will be destroyed, and the inhabitants of Judah will be rejected.